الجمل التي لها محل من الإعراب والجمل التي لا محل لها من الإعراب فی روایتي: (عصفور من الشرق) و (الرباط المقدس) لتوفیق الحكیم -دراسة نحوية دلالية- - مصطفى, أ.م.د. دانا أحمد; مجيد, طالب الماجستير(اللغة): رزگار أکرم (Sulaimani Journal for Humanities, 2023)
The ancient Arab grammarians and linguists did not delve deeper into their studies of the sentence in the way it deserved, it did not find that the point from which the grammarians started in their grammatical studies.the Arabic sentence revolved within the frame work of a specific mental conceptions based on special controls and foundations based on their division of the word, their understanding of the relationship between the parts of the sentences, the influence of each other, and hwo to arrange its parts, until it became a place the interest of modern Arab linguists, and they dealt it with research, study and analysis, and they defined it in different ways .In general, during their studies and research, gramarians dealt with the types of sentences, their division and functions, and according to the gramarians division of sentences, there are two types of them: sentences that have no place in parsing, and sentences that have place in parsing. This division is based on the possibility of interpreting the sentence in the singular. If it is not possible to interpret it, then it has no place in parsing, but if it is assigned to the singular, then in this case it has a place in parsing. If we take a close and careful look at the literary productions of (Tawfiq al-Hakim), we see that this writer did not neglect the structural, linguistic and semantic aspect in his novels, plays and stories. It has a place of parsing and sentences that have no place of parsing in his literary works, especially in his two novels: (OSFURUN MIN ALSHARQ) and (ALRIBAT ALMUQADAS), and try to employ them in the most beautiful way. Al-Hakim was able to employ the linguistic tool to generate meanings. The beautiful, with deep connotations, which indicates the writer's ability to comply with the meanings of the words, and to express what is going on in his mind with the most beautiful picture.